Concurrent Block Copolymer Polymersome Stabilization and Bilayer Permeabilization by Stimuli-Regulated "Traceless" Crosslinking - Wang, Xiaorui; Liu, Guhuan; Hu, Jinming; Zhang, Guoying; Liu, Shiyong (Angewandte Chemie International Edition, 2014)
The fabrication of block copolymer (BCP) vesicles (polymersomes) exhibiting synchronized covalent crosslinking and bilayer permeabilization remains a considerable challenge as crosslinking typically leads to compromised membrane permeability. Herein it is demonstrated how to solve this dilemma by employing a stimuli‐triggered crosslinking strategy with amphiphilic BCPs containing photolabile carbamate‐caged primary amines. Upon self‐assembling into polymersomes, light‐triggered self‐immolative decaging reactions release primary amine moieties and extensive amidation reactions then occur due to suppressed amine pKa within hydrophobic milieu. This leads to serendipitous vesicle crosslinking and the process is associated with bilayer hydrophobicity‐to‐hydrophilicity transition and membrane permeabilization. Two processes in one: A stimuli‐triggered crosslinking strategy was developed to concurrently crosslink and permeabilize block copolymer assemblies. Upon self‐assembling into polymersomes (see picture), light‐triggered self‐immolative decaging reactions release primary amine moieties and lead to extensive amidation reactions.